Determinants of Online Impulsive Buying Behaviour in Shopee E-Commerce (Study on Generation Z in Bali) - I Gusti Ayu Amalia Aryanti; I Made Wardana; I Gst. A. Kt. Gd. Suasana; Gede Bayu Rahanatha (Return : Study of Management, Economic and Bussines, 2025)
This study aims to analyze the effect of sales promotion, price discount, and hedonic motivation on online impulsive buying behavior, with positive emotion as a mediating variable, on Shopee e-commerce users from Generation Z in Bali Province. The approach used is associative quantitative with a survey method of 260 respondents selected through purposive sampling technique. Data collection was carried out using a questionnaire based on a Likert scale of 1-5, and data analysis using the Partial Least Square Structural Equation Modeling (SEM-PLS) method. The results showed that sales promotion, price discount, and hedonic motivation have a positive and significant effect on online impulsive buying behavior. In addition, these three variables also have a positive effect on positive emotion. Positive emotion is proven to have a significant influence on online impulsive buying behavior and partially mediates the relationship between sales promotion, price discount, and hedonic motivation on online impulse buying behavior. These findings support the Stimulus-Organism-Response (SOR) framework, which explains how external stimuli drive internal reactions in the form of positive emotions that ultimately trigger impulsive consumptive behavior. The implications of this study provide theoretical contributions in the development of SOR theory and practical contributions for e-commerce management, especially Shopee, in designing marketing strategies that are able to trigger positive emotions and encourage impulse purchases in the generation Z target market.